THE METHOD OF TRANSHIPMENT OF GOODS BETWEEN SHIPS IN OPEN SEA (STS) - Ali BAIAZIT; Serghei RADU; Gheorghe SAMOILESCU; Ciobanu Camelia (Fiabilitate şi Durabilitate)
The transhipment method is using a cable trolley system. The two ships are moving on parallel way inthe same direction, between them is suspended carrying the trolley wire. Transhipment of goods is made usingcontainer boxes which are caught by the trolley load jacks. The method offers the advantage of highproductivity, regardless of sea conditions. Basically, the system is usable at high degree of agitation of the sea.Slack in the cable carrier is assured by an automatic tension-adjusting device.